Optimisation of governmental decisions - Uzulina, Ginta (Journal of Business Economics and Management, 2003)
The report discusses the role of impact assessment and evaluation of governmental decisions. The main objective of report is to develop a statistical model for optimisation of the set of policy instruments. The Draft of Rural Development Plan is used as example in order to develop and test the statistical model for optimising the allocation and use of funds. The statistical model is developed like as a small software version for policy‐makers to evaluate critical decisions. The statistical decision making theory is used in seeking solutions to optimise the choice of governmental decisions. The functions of losses or gains are defined on the basis of statistical data in two levels ‐ macroeconomic level and microeconomic level. In the statistical model the principles of the subjective probability are also applied in the case of unreliable and unavailable information.First Published Online: 14 Oct 2010